2012
DOI: 10.1002/fedr.201200021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and ecogeography of Onobrychis viciifolia Scop. (Fabaceae) based on nrDNA ITS sequences and genomic ISSR fingerprinting

Abstract: In this study 40 specimens from 8 representative Iranian populations of Onobrychis viciifolia SCOP. were collected from their natural habitats. The specimens were biometrically assessed using 43 quantitative and 15 qualitative morphological characters. At each sample site we recorded ecogeographical variables. In order to evaluate the difference between the variation due to phenotypic responses and genetic adaptation, we generated nucleotide sequence data from the internal transcribed spacer of the nuclear rDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Onobrychis sensu Amirahmadi et al 2016 [ 15 ]) species such as O . viciifolia [ 42 , 43 ] and O . transsilvanica / O .…”
Section: Discussionmentioning
confidence: 99%
“…Onobrychis sensu Amirahmadi et al 2016 [ 15 ]) species such as O . viciifolia [ 42 , 43 ] and O . transsilvanica / O .…”
Section: Discussionmentioning
confidence: 99%
“…There were previous reports evaluating genetic structure and diversity in sainfoin populations/accessions. Some of them have used RAPD analysis (Nosrati et al, 2012;Rasouli et al, 2013;Hejrankesh et al, 2014;Ertus, 2021), ISSR analysis (Toluei et al, 2012;Zarrabian et al, 2013;Zarrabian and Majidi, 2015;Nosrati et al, 2016;Ertus, 2021), AFLP analysis (Bhattarai, 2017), and SSR analysis (Demdoum et al, 2012;Kempf et al, 2016;Ozkan and Bilgen, 2019;Shen et al, 2019;Sutcu, 2020). When the studies were examined, it was observed that either dominant marker systems or SSR analysis developed for closely related species were used for determination of the genetic structure and diversity of sainfoin species.…”
Section: Introductionmentioning
confidence: 99%